2021
DOI: 10.3390/min11020132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of FeCu Bimetallic Nanoparticles in Coal Mine Wastewater Treatment

Abstract: Wastewater treatment has become a global challenge with wastewater treatment cost fast increasing. Industrial processes such as downstream processes, wastewater treatment, and several fermentation processes depend largely on the use of flocculants. Synthetic flocculants, which are conventionally used in wastewater treatment, are hazardous to the environment and are carcinogenic to human health. Therefore, bioflocculants can be used as an alternative due to their biodegradable and environmentally friendly natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…On the other hand, Amen et al [ 17 ] proposed adsorption followed by reductive reaction mechanisms to describe the COD degradation in the presence of nZVI/Cu 0 . Recently, Dlamini et al [ 48 ] found that FeCu exhibited flocculation activity in treating coal mine wastewater which was rich in phosphate, calcium, sulphate, COD, and BOD. Thus, the removal of COD in this study could be due to the combined effect of adsorption, reductive reaction, and flocculation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Amen et al [ 17 ] proposed adsorption followed by reductive reaction mechanisms to describe the COD degradation in the presence of nZVI/Cu 0 . Recently, Dlamini et al [ 48 ] found that FeCu exhibited flocculation activity in treating coal mine wastewater which was rich in phosphate, calcium, sulphate, COD, and BOD. Thus, the removal of COD in this study could be due to the combined effect of adsorption, reductive reaction, and flocculation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were also reported by Mahmoud et al, [ 20 ] where COD was reduced from 600 to 76 ppm, while BOD was reduced from 365 to 31 ppm when the raw wastewater from San Elhagr Al‐Sharqia, Egypt, was treated with nano‐zero valence iron (nZVI). Recently, Dlamini et al [ 21 ] reported that 92% of COD and 97% of BOD were removed from coal mine wastewater using FeCu bimetallic nanoparticles as a flocculant. Nevertheless, the mechanism of organic compound removal by bimetallic nanoparticles has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, two volumes of ethanol was added, and the mixture was allowed to precipitate at 4 °C for 12 h. Afterwards, the precipitate was vacuum-dried, and the crude product was re-dissolved in the sterilised distilled water to give a solution of 1%. In order to purify the bioflocculant, a mixture of chloroform and n-butyl alcohol (5:2 v/v) was pipetted into the bioflocculant solution in a ratio of 2:1 (v/v) and the mixture was left at room temperature for 12 h. The resultant precipitate was collected and vacuum-dried [ 30 ].…”
Section: Methodsmentioning
confidence: 99%